Persepsi Perawat Dalam Melengkapi Dokumentasi Keperawatan: Nurses' Perceptions In Completing Nursing Documentation - Suciani , Tiertania Mega; Ratnasari; Yanto, Arief (Jurnal Keperawatan Sumba (JKS), 2024)
Nursing documentation serves as an essential indicator of nursing care implementation, providing evidence of a nurse’s report on a patient’s health progress. Nursing documentation serves various purposes, including administrative, medical, legal, financial, research, educational, accreditation, statistical, and communication purposes. Incomplete nursing documentation can adversely impact patient safety and nurses themselves. Currently, nurses’ understanding of nursing documentation remains suboptimal. A recent question-and-answer session with several ICU nurses at SMC RS Telogorejo revealed that one of the barriers to completing nursing documentation is nurses’ lack of clear understanding of how to document using computerized systems. This study employed an analytical design with a cross-sectional approach. The population consisted of all ICU nurses at SMC RS Telogorejo, totaling 42 individuals. The sampling technique used was total sampling, resulting in a sample size of 42 nurses. The research instruments included a demographic data questionnaire and a Nurse Perception Questionnaire on Completing Nursing Documentation. The research findings indicate that nurses’ perception of completing nursing documentation is mostly positive, with 41 individuals (97.6%) having a favorable perception. Factors supporting and hindering nurses in completing nursing documentation include nurses’ ability to document according to nursing standards, sufficient availability of devices, ease of applying computer-based nursing documentation programs, and regular training and supervision in computer-based nursing documentation. This study contributes to nursing knowledge and serves as a reference for enhancing the understanding of nurses’ perceptions regarding completing nursing documentation.